2020
DOI: 10.3390/molecules25173945
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling the Photoprotective Mechanisms of Nature-Inspired Ultraviolet Filters Using Ultrafast Spectroscopy

Abstract: There are several drawbacks with the current commercially available ultraviolet (UV) filters used in sunscreen formulations, namely deleterious human and ecotoxic effects. As a result of the drawbacks, a current research interest is in identifying and designing new UV filters. One approach that has been explored in recent years is to use nature as inspiration, which is the focus of this review. Both plants and microorganisms have adapted to synthesize their own photoprotective molecules to guard their DNA from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 141 publications
0
39
0
Order By: Relevance
“… Schematic of a typical transient electronic absorption spectroscopy (TEAS) setup. Reprinted with permission from ref ( 38 ). Copyright 2020 MDPI.…”
Section: Experimental Techniquesmentioning
confidence: 99%
“… Schematic of a typical transient electronic absorption spectroscopy (TEAS) setup. Reprinted with permission from ref ( 38 ). Copyright 2020 MDPI.…”
Section: Experimental Techniquesmentioning
confidence: 99%
“…In fact, most of UV filters are inspired in natural products, specifically of botanical, animal, or mineral origin [ 5 ]. In 1928, benzyl salicylate was discovery for its photoprotective action against UVB radiation, but it was only commercialised in 1935 in the first sunscreen “Ambre Solaire” [ 6 , 7 ]. Later, almost 50 years, avobenzone and its derivatives appeared as the first UV filters that ensure protection against UVA radiation [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the many sunscreen formulations currently available, certain setbacks such as the potential toxicity to humans and the environment, as well as photo-instability, have resulted in the banning of some UV filters [7][8][9][10]. To this effect, sunscreen scientists have continued to search for safe and efficient UV filters, seeking inspiration from natural sources, including plants and microorganisms [11]. For example, in plants, sinapoyl malate (SM, see Figure 1A), found in the upper layer of Brassicaceous plants such as thale cress (Arabidopsis thaliana), has been reported to be the photoprotective agent [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…For example, in plants, sinapoyl malate (SM, see Figure 1A), found in the upper layer of Brassicaceous plants such as thale cress (Arabidopsis thaliana), has been reported to be the photoprotective agent [12,13]. In order to elucidate the photoprotection mechanism, the photodynamics of SM and its derivatives have also been studied [11,[14][15][16][17][18][19]. Briefly, these studies have shown that following UV absorption, SM and its derivatives undergo an efficient and ultrafast energy relaxation mechanism, predominantly trans-to-cis photoisomerisation, which accounts for their longterm photostability and photoprotective nature.…”
Section: Introductionmentioning
confidence: 99%